Developing Students’ Character through Integrated Anti-Corruption Education - Baharuddin Baharuddin; Ita Sarmita Samad (Edumaspul: Jurnal Pendidikan, 2019)
Corruption has become an acute problem for the Indonesian people since independence. Various efforts have been made to hack the corruption problem but have not succeeded. The cultural approach would be a solution to the problem. The cultural approach in question is education. Through education, prevention of corruption can be done by creating a healthy environment, strengthening character, and internalizing the noble values ​​in daily behavior for students. Strengthening of character is reflected by cultivating shame, socialization about the importance of honest culture and the bad of cheating both directly and indirectly. Termsuk by making the "Honesty Canteen" to build the honest value habituation of the students. Another effort that can be done is to integrate anti-corruption education in the subjects taught at school. In anti-corruption education must integrate three main domains, namely the domain of knowledge (cognitive), attitudes and behavior (affection), and skills (psychomotor). Implementation of anti-corruption education at the school level can use an integrative-inclusive strategy (inserted in existing subjects) and exclusive (special/individual subjects).